The Form and Pattern of Business Actors Requirements in Exclusive Dealing: A Rule of Reason Approach - Tri Anggraini, Anna Maria; Sabirin, Ahmad; Rumahorbo, Yoel Nixon A (Yustisia, 2023)
Tying is usually defined as the dominant company selling one product since the buyer must also purchase a different product or agree not to purchase the bonded product from other suppliers. This paper analyzes requirements imposed by the reported business actor on other parties deemed to have violated the tying and bundling under competition law in Indonesia, the U.S., and the European Union. Also, it discusses the application of the Rule of Reason by the competition commission in these three region. This study uses a comparative law approach. The results of the analysis show that a tying agreement is an agreement that requires the recipient of the supply to buy other products that are not necessarily needed. Usually, these agreements are entered into by two affiliated companies or at least cooperating partners, one of which occupies a dominant position to prevent competitors from entering the relevant market. Not all tying agreements have a negative impact. Therefore, an impact analysis is needed through a rule of reason approach, especially in digital-based industries.